RESEARCH ON THE IMPACT OF READING ON THE LEVEL OF ANXIETY OF STUDENTS IN WAR CONDITIONS (Psychology Travelogs, 2024)
The article provides a brief overview of studies of the emotional states of student youth during the war.It was found that such extreme conditions as war are characterized by a high level of emotional tension, which, in turn, produces the following emotional states: fear, panic, anxiety, stress, frustration. These states negatively affect the general well-being of the individual and are reflected in the instability of emotional response.It is shown that during the full-scale invasion, the emotional states of the Ukrainian population and students in particular worsened, in particular, the level of anxiety, depression, emotional instability increased, and resistance to stress factors decreased. This prompted the search for existing psychological tools that can be used as accessible self-help.Scientific works on the possibilities of the positive impact of reading on the human psyche were analyzed. Accordingly, an own empirical study was organized and conducted, aimed at studying the impact of reading on emotional states, in particular anxiety, of student youth during the war. The results of this empirical study on the impact of reading on the emotional states of young people are presented in a generalized form. It was found that, according to the method of measuring the level of anxiety of Taylor in the adaptation of T. Nemchynov, reading students are less anxious than non-reading ones. Reading students also have a better mood, less aggression, frustration, rigidity.Prospects for further research in this direction consist in a more detailed study of the impact of reading on other emotional states of students, in particular by gender, professional orientation, course of study. It is also important to develop recommendations for the use of reading as a means of self-help to improve the emotional state of student youth in war conditions.
Keywords: emotional state; reading; students; psychological self-help; emotions; anxiety; war